The flipped-classroom effect on vocational high school students’ learning outcomes - Admaja Dwi Herlambang; Ririn Ririn; Aditya Rachmadi (International Journal of Evaluation and Research in Education (IJERE), 2024)
The flipped-classroom instructional model is considered suitable for teaching procedural knowledge. Apart from flipped-classroom, it turns out that another instructional model, namely direct instruction, is also designed to teach procedural knowledge. Therefore, this study aimed to examine differences in procedural knowledge learning outcomes between flipped-classroom and direct instruction learning models in the cognitive and psychomotor domains and to determine the effect of flipped-classroom on students’ procedural knowledge learning outcomes. This type of research is a true-experimental design with a randomized pre-test post-test control group design for the cognitive domain and a randomized post-test only control group design for the psychomotor domain. The research instrument used a written test (pre-test and post-test) for the cognitive domain and a performance assessment for the psychomotor domain. The flipped-classroom is better than direct instruction regarding procedural knowledge learning outcomes. Furthermore, flipped-classroom significantly affects the students’ procedural knowledge learning outcomes, both cognitive and psychomotor domains. The effect of flipped-classroom implementation on the psychomotor domain (t(50)=23.62; p<0.01; d=6.56) is greater than the impact of performance on the cognitive domain (t(50)=2.35; p<0.05; d=0.65).